Tectonic-thermal history and hydrocarbon potential of the Pearl River Mouth Basin, northern South China Sea: Insights from borehole apatite fission-track thermochronology - Xiao-yin Tang; Shu-chun Yang; Sheng-biao Hu (China Geology)
ABSTRACT: The Pearl River Mouth Basin (PRMB) is one of the most petroliferous basins on the northern margin of the South China Sea. Knowledge of the thermal history of the PRMB is significant for understanding its tectonic evolution and for unraveling its poorly studied source-rock maturation history. Our investigations in this study are based on apatite fission-track (AFT) thermochronology analysis of 12 cutting samples from 4 boreholes. Both AFT ages and length data suggested that the PRMB has experienced quite complicated thermal evolution. Thermal history modeling results unraveled four successive events of heating separated by three stages of cooling since the early Middle Eocene. The cooling events occurred approximately in the Late Eocene, early Oligocene, and the Late Miocene, possibly attributed to the Zhuqiong II Event, Nanhai Event, and Dongsha Event, respectively. The erosion amount during the first cooling stage is roughly estimated to be about 455–712 m, with an erosion rate of 0.08–0.12 mm/a. The second erosion-driven cooling is stronger than the first one, with an erosion amount of about 747–814 m and an erosion rate between about 0.13–0.21 mm/a. The erosion amount calculated related to the third cooling event varies from 800 m to 3419 m, which is speculative due to the possible influence of the magmatic activity.©2023 China Geology Editorial Office.